Comparison of shuttle walk with measured peak oxygen consumption in patients with operable lung cancer. Issue 1 (21st October 2005) - Win, T; Jackson, A; Groves, A M; Sharples, L D; Charman, S C; Laroche, C M
Abstract : Background: The relationship between the shuttle walk test and peak oxygen consumption in patients with lung cancer has not previously been reported. A study was undertaken to examine this relationship in patients referred for lung cancer surgery to test the hypothesis that the shuttle walk test would be useful in this clinical setting. Methods: 125 consecutive patients with potentially operable lung cancer were prospectively recruited. Each performed same day shuttle walking and treadmill walking tests. Results: Shuttle walk distances ranged from 104 m to 1020 m and peak oxygen consumption ranged from 9 to 35 ml/kg/min. The shuttle walk distance significantly correlated with peak oxygen consumption ( r = 0.67, p<0.001). All 55 patients who achieved more than 400 m on the shuttle test had a peak oxygen consumption of at least 15 ml/kg/min. Seventy of 125 patients failed to achieve 400 m on the shuttle walk test; in 22 of these the peak oxygen consumption was less than 15 ml/kg/min. Nine of 17 patients who achieved less than 250 m had a peak oxygen consumption of more than 15 ml/kg/min. Conclusion: The shuttle walk is a useful exercise test to assess potentially operable lung cancer patients with borderline lung function. However, it tends to underestimate exercise capacity at the lower range compared with peak oxygen consumption. Our data suggest that patients achieving 400 m on the shuttle walk test do not require formal measurement of oxygen consumption. In patients failing to achieve this distance we recommend assessment of peak oxygen consumption, particularly in those unable to walk 250 m, because a considerable proportion would still qualify for surgery as they had an acceptable peak oxygen consumption.